Coupling Respirometric HER and ORR Monitoring with Electrochemical Measurements - Strebl, Michael; Bruns, Mark; Virtanen, Sannakaisa (Electrochimica Acta, 2022)
An experimental setup for respirometric real-time monitoring of the kinetics of the H2 evolution reaction and the O2 reduction reaction coupled with electrochemical control is presented. Cathodic polarization of different metal electrodes was carried out to verify the accuracy, and sensitivity of this approach. It was found that the respirometric response was in excellent agreement with the applied electrical signal. Dissolution of H2 in the liquid phase can lead to a delayed detection of the evolved H2 in the gas phase. However, reducing the volume of electrolyte in the setup can diminish this lag in response time. The influence of H2 oxidation on reactive Pt and the generation of H2O2 on Au on the respirometric monitoring of cathodic reactions was investigated. Finally, the combined respirometric and electrochemical approach was applied to quantify dissolution of Al during cathodic polarization by relating the total cathodic charge with the electrical signal.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Cathodic corrosion; Electrode kinetics; HER and ORR real-time monitoring; Respirometric Method